2007
DOI: 10.1210/jc.2007-0544
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Increases Final Height in Patients with Juvenile Idiopathic Arthritis: Data from a Randomized Controlled Study

Abstract: Our data suggest that long-term GH therapy has a beneficial effect on growth and final height in the majority of growth retarded children with severe forms of JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 17 publications
3
41
0
3
Order By: Relevance
“…Only 4 of 18 patients (22%) reached a final height within their target height range. Multiple regression analyses revealed that the standardized height gain was most influenced by mean erythrocyte sedimentation rate, mean C-reactive protein level and mean prednisolone dose (cumulative R 2 with 0.67, p < 0.05) [9]. The tremendous height SDS loss during the prepubertal years in this patient group is comparable to retrospective data reported by Simon et al [1].…”
Section: Growth In Patients With Jiasupporting
confidence: 72%
“…Only 4 of 18 patients (22%) reached a final height within their target height range. Multiple regression analyses revealed that the standardized height gain was most influenced by mean erythrocyte sedimentation rate, mean C-reactive protein level and mean prednisolone dose (cumulative R 2 with 0.67, p < 0.05) [9]. The tremendous height SDS loss during the prepubertal years in this patient group is comparable to retrospective data reported by Simon et al [1].…”
Section: Growth In Patients With Jiasupporting
confidence: 72%
“…In another study, GH treatment was reported to be most effective in rescuing bone growth in those childhood JIA patients with moderate disease activity (Bechtold et al 2007). …”
Section: Prevention Of Growth Retardation Caused By Chronic Inflammationmentioning
confidence: 98%
“…Corticosteroid consumption was part of the secondary outcome measures in 25 trials (18.0%). A statistical analysis adjusted for corticosteroid use was described as planned in 2 other reports (1.5%), based on a Cox proportional hazards model adjusted for concomitant use of corticosteroids (10) or exploratory analysis of covariance adjusted for mean daily corticosteroid dosage (11).…”
Section: Resultsmentioning
confidence: 99%